A water-soluble supramolecular complex that mimics the heme/copper hetero-binuclear site of cytochrome c oxidase12. Issue 7 (23rd January 2018) - Kitagishi, Hiroaki; Shimoji, Daiki; Ohta, Takehiro; Kamiya, Ryo; Kudo, Yasuhiro; Onoda, Akira; Hayashi, Takashi; Weiss, Jean; Wytko, Jennifer A.; Kano, Koji
Abstract : The O2 adduct of an aqueous synthetic heme/copper model system built on a porphyrin/cyclodextrin supramolecular complex has been characterized. Abstract : In mitochondria, cytochrome c oxidase (C c O) catalyses the reduction of oxygen (O2 ) to water by using a heme/copper hetero-binuclear active site. Here we report a highly efficient supramolecular approach for the construction of a water-soluble biomimetic model for the active site of C c O. A tridentate copper(ii ) complex was fixed onto 5, 10, 15, 20-tetrakis(4-sulfonatophenyl)porphinatoiron(iii ) (Fe III TPPS) through supramolecular complexation between Fe III TPPS and a per- O -methylated β-cyclodextrin dimer linked by a (2, 2′:6′, 2′′-terpyridyl)copper(ii ) complex (Cu II TerpyCD2 ). The reduced Fe II TPPS/Cu I TerpyCD2 complex reacted with O2 in an aqueous solution at pH 7 and 25 °C to form a superoxo-type Fe III –O2 − /Cu I complex in a manner similar to C c O. The pH-dependent autoxidation of the O2 complex suggests that water molecules gathered at the distal Cu site are possibly involved in the Fe III –O2 − /Cu I superoxo complex in an aqueous solution. Electrochemical analysis using a rotating disk electrode demonstrated the role of the FeTPPS/CuTerpyCD2 hetero-binuclear structure in the catalytic O2 reduction reaction.